2012
DOI: 10.5588/ijtld.11.0110
|View full text |Cite
|
Sign up to set email alerts
|

Survival of HIV-infected patients after starting tuberculosis treatment: a prospective cohort study

Abstract: The use of HAART can prevent deaths among HIV-TB patients, corroborating the efficacy of starting HAART early in individuals with TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
12
2
3
Order By: Relevance
“…Gender was associated with progression to AIDS; the hazard of AIDS among women was significantly higher than among men, as previously reported by others [1,12,27]. Also the survival rate from AIDS to death was not any more significant as previously stated by others [4,13,22,27]. However, based on the study carried out by Mirzaei et al, the survival rate from AIDS to death was higher for women than in men [12].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Gender was associated with progression to AIDS; the hazard of AIDS among women was significantly higher than among men, as previously reported by others [1,12,27]. Also the survival rate from AIDS to death was not any more significant as previously stated by others [4,13,22,27]. However, based on the study carried out by Mirzaei et al, the survival rate from AIDS to death was higher for women than in men [12].…”
Section: Discussioncontrasting
confidence: 50%
“…One year and five year survival rates from AIDS to death were 76% and 46%, respectively [12]. A prospective cohort study which was carried out by Maruza et al in 2012 in Brazil showed that the probability of 30 months survival among HIV-infected patients was 70% [22]. Spagnuoloet al performed a retrospective cohort study in Italy in 2012 and showed that 10 year survival of HIV infected subjects with non-AIDS-defining malignancies was 44.7% [23].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the Brazilian policy has been the object of nationwide studies, mostly focused on mortality [9], [10], [14], [15], the impact on the health system [1], [5], [16] and HIV resistance surveillance [17], [18], as well as small studies with limited representativeness, evaluating the clinical aspects of HIV infection [8], [11], [19] and the use of cART [20][24]. However, to date, there have been no nationwide longitudinal studies providing a broader picture of the Brazilian HIV epidemic and the results of the national HIV policy.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of TB, as well as the use of HAART, improves prognosis, as its late onset in patients with a previously confirmed diagnosis of TB increases mortality; which highlights the importance of good immunological control in HIV patients. 6,8 TB in Spain may be more common in immigrants. In our study there were 2 patients from Pakistan and one from Eastern Europe, although the only patient that died was native.…”
Section: Discussionmentioning
confidence: 99%
“…4 Conversely, a reduction in the incidence of S. peumoniae invasive disease (bacteremia) has been observed. 5 Pulmonary tuberculosis (TBC) has always been a worldwide health problem with a great impact in the pre-HAART era, in HIV/AIDS population [6][7][8][9] even in the developed world. Nowadays, pulmonary tuberculosis develops in HIV patients with relatively good immunological control and its incidence has become close to that of the immunocompetent population of the same geographical area.…”
Section: Introductionmentioning
confidence: 99%